Tell the wolves I'm home [compact disc, unabridged] : a novel - Brunt, Carol Rifka (Blackstone Audio, 2012)
It is 1987, and only one person has ever truly understood fourteen-year-old June Elbus -- her uncle, the renowned painter Finn Weiss. Shy at school and distant from her older sister, June can only be herself in Finn's company; he is her godfather, confidant, and best friend. So when he dies, far too young, of a mysterious illness her mother can barely speak about, June's world is turned upside down. But Finn's death brings a surprise acquaintance into June's life -- someone who will help her to heal, and to question what she thinks she knows about Finn, her family, and even her own heart.